2012
DOI: 10.1007/s00417-012-1947-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of deep anterior lamellar keratoplasty for active or quiescent herpetic stromal keratitis

Abstract: DALK can not only remove the corneal lesions of HSK but also reduce latent or persistent viral loads in the cornea. In eyes with active or quiescent HSK but otherwise healthy endothelia, DALK seems to be safe and promising for its favorable visual outcome, graft survival rate, and low endothelial cell loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Patients with a history of corneal trauma or use of topical glucocorticoids, which are the main risk factors for FK, combined with the clinical features of FK were at high suspicion of having FK . The primary diagnosis of herpes simplex keratitis (HSK) was made according to a history of recurrent episodes of HSK combined with the typical clinical features of HSK . According to the clinical features, 34 patients were at high suspicion of having FK, five were at high suspicion of having HSK, 21 were only primarily diagnosed with corneal ulcer with an unidentified pathogen, and seven were diagnosed with graft ulcer after keratoplasty.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a history of corneal trauma or use of topical glucocorticoids, which are the main risk factors for FK, combined with the clinical features of FK were at high suspicion of having FK . The primary diagnosis of herpes simplex keratitis (HSK) was made according to a history of recurrent episodes of HSK combined with the typical clinical features of HSK . According to the clinical features, 34 patients were at high suspicion of having FK, five were at high suspicion of having HSK, 21 were only primarily diagnosed with corneal ulcer with an unidentified pathogen, and seven were diagnosed with graft ulcer after keratoplasty.…”
Section: Methodsmentioning
confidence: 99%
“…15 Another report demonstrated that the endothelial cell count 6 and 12 months after DALK was 1908 6 516 cells per square millimeter and 1835 6 491 cells per square millimeter, respectively. 25 Our results showed that the endothelial cell count after a mean follow-up of 50 months was 1738 6 573 cells per square millimeter, even when the preoperative corneal scars reached near the level of DM. These results were encouraging because our follow-up time was much longer than that of the previous studies.…”
Section: Discussionmentioning
confidence: 45%
“…[14] In order to alleviate patient pain, rehabilitate visual acuity, and recover corneal clarity, therapeutic corneal transplantation is needed to eliminate most of the virus existing in the stroma, and thus, reduce the viral load. [20] …”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the theory that grafts survive better in inactive HSK when compared with active cases. [34,35] Wang et al [20] demonstrated that HSV antigens were identified in 84.2% of the active cases, but 15.4% of the inactive cases via immunohistochemistry staining. Based on the above information, GCCTs can be effectively and biosafely used with a low rejection and recurrence rate in DALK.…”
Section: Discussionmentioning
confidence: 99%